Introducing the Irish Evaluation Network - Connor Sullivan (The Evaluation Center at Western Michigan University, 2007)
The Irish Evaluation Network (IEN) is a network for individuals involved or interested in forwarding the theory and practice of high quality evaluation in an Irish context. Established in 2002, to date it has operated as an informal network guided by a voluntary steering group